2020
DOI: 10.1016/j.apenergy.2020.114822
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjustment strategies on building design process in different climates oriented by multiple performance

Abstract: The effect of the adjustment strategy on the building design process is analyzed. • Uncertainty analysis, sensitivity analysis, performance optimization are involved. • Shading, window ventilation, and dimming are considered in the adjustment strategy. • Energy, thermal and visual comfort are included in building performance. • Various climate zones in China are compared given the impact of climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 65 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…Meanwhile, VME is different from the education of other music disciplines, which is a very abstract education and not intuitive except for the external singing performance. Therefore, people deem VME the most challenging musical course in higher institutions [ 1 , 2 ]. Particularly, VME in Chinese higher institutions has gone through four periods: germination period, development period, slow period, and climax period.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, VME is different from the education of other music disciplines, which is a very abstract education and not intuitive except for the external singing performance. Therefore, people deem VME the most challenging musical course in higher institutions [ 1 , 2 ]. Particularly, VME in Chinese higher institutions has gone through four periods: germination period, development period, slow period, and climax period.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the first direction of lighting optimizations, it can be classified into three major groups (i.e., a, b, and c). Research efforts in group (a) [29,[99][100][101][102][103] addressed modification strategies of design parameters and the ability of optimization techniques to deal with that issue. In this regard, Kim and Chung [99] presented a daylighting simulation model combined with the architectural design process to obtain high-precision simulations leading to high-performance architectural designs.…”
Section: Lighting Optimization Modelsmentioning
confidence: 99%
“…Furthermore, Acosta et al [102] conducted multiple simulations on room designs using three different shapes of skylights under overcast-sky conditions by the Lightscape simulation program to identify the most appropriate shape of lightscoop skylights. Wang et al [103] adopted a gradient boosted decision trees-based non-dominated sorting genetic algorithm integrated with EnergyPlus in the Python environment to address the influence of window ventilation and shading on multi-objective building design optimization process under different climate conditions. They concluded that with multi-objective optimization strategies, it is possible to achieve 38.1% of energy savings in severely cold weather and 17.6% of improved comfort in both summer and winter conditions.…”
Section: Lighting Optimization Modelsmentioning
confidence: 99%
“…Analyzing the coupling relationship between people and architectural space needs to consider people's life behavior and life scene. Residential behavior affects the interior design of buildings and the energy consumption of structures [ 1 , 2 ]. Parametric design is a new development stage of digital design, which aims to adapt the prototype to the design goal through the collection operation of the prototype.…”
Section: Introductionmentioning
confidence: 99%